PENGEMBANGAN LKS (LEMBAR KERJA SISWA) FISIKA BERBASIS CTL (CONTEXTUAL TEACHING AND LEARNING) UNTUK MENINGKATKAN COLLABORATIVE SKILLS SISWA DI SMA - Ika Ayu Puspita; Sri Wahyuni; Yushardi Yushardi (JURNAL PEMBELAJARAN FISIKA, 2017)
This research was the development research to produce science SWS(Students Work Sheet) based CTL (Contextual Teaching and Learning) that willimprove collaborative skills of students on the subject of elasticity and Hooke’s lawthat aims to: 1) validation SWS based CTL, 2) result of collaborative skills, 3) resultof learning activities. The research design was the design of 4-D model (define,design, develop, and destiminate) by Thiagarajan, Semmel and Semmel (1974)which modified into 3-D, 4-D model which is limited only at development stage. Thedestiminate stage is not implemented due to limited time and cost. The results of thisresearch were: validation SWS (Student Work Sheet) physics based on CTL(Contextual Teaching and Learning) reached 75,62%, with a valid category; resultof collaborative skills reached 84.93% with a very effective category; and result oflearning activities reached 91.18% so classified very practial.Keywords: SWS (Students Work Sheet), CTL, collaborative skills